2005 5th International Conference on Information Communications &Amp; Signal Processing
DOI: 10.1109/icics.2005.1689223
|View full text |Cite
|
Sign up to set email alerts
|

Review of Rain Attenuation Studies in Tropical and Equatorial Regions in Brazil

Abstract: This paper presents a review of rain attenuation studies based on measurements performed since 1987 in tropical and equatorial regions of Brazil. The terrestrial measurements include long term measurements for frequencies between 11 and 38 GHz at 20 links. The satellite measurements have been performed in the Ku band using radiometers and beacon receivers at 10 sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The rainfall rate and rain attenuation data for the Brazilian tropical climate were sourced from [12]. The measured point rainfall rate CD of Rio de Janeiro, Brazil, is reproduced in Figure 6a, while the characteristics of the five terrestrial links over which rain attenuation was measured are shown in Table 2.…”
Section: R a I N A T T E N U A T I O N ( D B ) P E N A N G J O H O R mentioning
confidence: 99%
“…The rainfall rate and rain attenuation data for the Brazilian tropical climate were sourced from [12]. The measured point rainfall rate CD of Rio de Janeiro, Brazil, is reproduced in Figure 6a, while the characteristics of the five terrestrial links over which rain attenuation was measured are shown in Table 2.…”
Section: R a I N A T T E N U A T I O N ( D B ) P E N A N G J O H O R mentioning
confidence: 99%
“…Noted that the remarkably low year to year variability of the annual cumulative distributions for the two years over the 0.1% exceedance range detected in Malaysia. The data measured in Abakaliki, Nigeria (Omotosho and Oluwafemi, 2009) and in Rio de Janeiro, Brazil (Pontes et al, 2005), both in equatorial region, show considerably more fading than Malaysia. With the variety of rain climates to be characterized, considerably more data are thus required for the development of satisfactory physically based models for prediction.…”
Section: Cumulative Distribution For Diurnal Variabilitymentioning
confidence: 99%
“…Generally, the required inputs in most attenuation prediction models for terrestrial point-to-point microwave links are the rainfall rate exceeded at p % of time, the effective propagation path length and the link's operating frequency [7], [16]. Thus p…”
Section: Theoretical Background Of Rain Attenuation Prediction Momentioning
confidence: 99%
“…An overview of Lin model [7], revised Moupfouma model [8], revised Silva Mello model [9] and the newly released ITU-R model [10] is briefly presented in the following subsections.…”
mentioning
confidence: 99%
See 1 more Smart Citation